Effect of Fermented Rice Bran in the Ration on Weight and Percentage of Carcass and Non-Carcass Male Quail 7 Weeks Old - Donbosko Arung Ramelau Hamapati; Ni Ketut Mardewi; I Gusti Ayu Dewi Seri Rejeki (Warmadewa University Press, 2022)
The community widely uses the demand for livestock products such as meat because they have good taste and high nutritional content. One source of meat is quail meat. Quail meat has a high nutritional value and is not inferior to other poultry. Quail (Coturnix coturnix japonica) is one of the poultry commodities that has a role in producing animal protein. The purpose of this study was to determine the effect of giving fermented rice bran in the ratio to the weight and percentage of carcasses as well as the weight and percentage of non-carcass male quail aged seven weeks and to determine the level of giving fermented rice bran in the diet of male quail to the best weight and percentage of carcasses and weight and percentage of non-carcass male quail aged seven weeks. The study was conducted using a completely randomized design (CRD) with five treatments and three replications. Each replication consisted of 3 male quail so that the number of male quails used was 45. The treatments were applied as follows, rations with unfermented rice bran 20% and rations with fermented rice bran 5%, 10%, 15%, and 20%. Parameters observed were slaughter weight, carcass weight, non-carcass weight, carcass percentage, and non-carcass percentage. The data obtained were analyzed for variance. If there are significantly different results (P <0.05) between treatments, Duncan's smallest total distance test is carried out. The study results show that the administration of fermented rice bran in the male quail aged seven weeks showed no significant difference (P>0.05) on cut weight, carcass weight, non-carcass weight, carcass percentage, and non-carcass percentage. Based on the results of this study, it can be suggested in making male quail rations to use fermented rice bran to a level of 15% because it can increase the protein content of the ration and can increase slaughter weight, carcass weight, and carcass percentage as well as in rice bran fermentation it is necessary to use another fermenter so that protein rice bran becomes higher so that the protein ration increases and is also expected to reduce the crude fiber content of the ration